2020
DOI: 10.1182/bloodadvances.2019000467
|View full text |Cite
|
Sign up to set email alerts
|

GRK6 regulates the hemostatic response to injury through its rate-limiting effects on GPCR signaling in platelets

Abstract: Key points GRK6 regulates the hemostatic response by limiting platelet activation via thrombin and adenosine 5′-diphosphate. GRK6 regulates the hemostatic response by reducing PAR1/4- and P2Y12-dependent signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 42 publications
0
29
1
Order By: Relevance
“…Using CRISPR-Cas9 genome editing, we generated a GRK6 knockout mouse mutant line. We have shown that loss of GRK6 in mouse platelets increases both PAR4 and P2Y 12 -dependent signaling [25]. Notably, deletion of GRK6 has an effect on mouse PAR4-dependent signaling but not human PAR4-dependent signaling.…”
Section: Regulation Of Thrombin Receptor Signaling By Grk6mentioning
confidence: 85%
See 4 more Smart Citations
“…Using CRISPR-Cas9 genome editing, we generated a GRK6 knockout mouse mutant line. We have shown that loss of GRK6 in mouse platelets increases both PAR4 and P2Y 12 -dependent signaling [25]. Notably, deletion of GRK6 has an effect on mouse PAR4-dependent signaling but not human PAR4-dependent signaling.…”
Section: Regulation Of Thrombin Receptor Signaling By Grk6mentioning
confidence: 85%
“…Messenger RNA and predicted protein copy number analysis in human and mouse platelets have identified the presence of GRK expression [21][22][23]. Further study using immunoblotting has confirmed the expression of specific GRKs (GRK2, GRK5, and GRK6) in platelets [24][25][26]. In human platelets, GRK2, GRK5, and GRK6 are all expressed in the range of 1000-2000 copies per platelet, with GRK6 having the highest expression level.…”
Section: Grks In Plateletsmentioning
confidence: 89%
See 3 more Smart Citations